2023
DOI: 10.1002/adfm.202213856
|View full text |Cite
|
Sign up to set email alerts
|

Red Emissive Carbon Dot Superoxide Dismutase Nanozyme for Bioimaging and Ameliorating Acute Lung Injury

Abstract: Harnessing the physiochemical properties and enzymatic activities of nanozymes will provide new insights for disease theranostics. Herein, a novel carbon dot (C‐dot) superoxide dismutase (SOD) nanozyme that exhibits red fluorescence with emission wavelength of 683 nm and shows high SOD‐like activity of >4000 U mg−1 is reported, which presents the great potential for imaging the biodistribution of nanozyme itself in vivo and ameliorating acute lung injury. Through surface modifications, the mechanism of C‐dot S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 61 publications
1
70
0
Order By: Relevance
“…The high-resolution XPS spectra of Ti in NFC/TiO 2 (Figure g) exhibited binding energies at 464.1 and 458.4 eV, ascribed to Ti 2p 1/2 and Ti 2p 3/2 , respectively, and were in agreement with those observed in the TiO 2 sample . Notably, no apparent N 1s signal was detected in TiO 2 (Figure h), while an evident N 1s peak emerged upon NFC functionalization, which was deconvoluted into three peaks with binding energies at 400.2, 399.8, and 399.1 eV, corresponding to N–(C) 3 , N–H, and N–(H) 2 , respectively. Additionally, the XPS spectra of O 1s (Figure i) contained four peaks: 531.8 and 529.6 eV were assigned to Ti–OH and Ti–O bonds in TiO 2 , while 533.7 and 531.2 eV corresponded to C–O and CO in the NFC molecule. , …”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The high-resolution XPS spectra of Ti in NFC/TiO 2 (Figure g) exhibited binding energies at 464.1 and 458.4 eV, ascribed to Ti 2p 1/2 and Ti 2p 3/2 , respectively, and were in agreement with those observed in the TiO 2 sample . Notably, no apparent N 1s signal was detected in TiO 2 (Figure h), while an evident N 1s peak emerged upon NFC functionalization, which was deconvoluted into three peaks with binding energies at 400.2, 399.8, and 399.1 eV, corresponding to N–(C) 3 , N–H, and N–(H) 2 , respectively. Additionally, the XPS spectra of O 1s (Figure i) contained four peaks: 531.8 and 529.6 eV were assigned to Ti–OH and Ti–O bonds in TiO 2 , while 533.7 and 531.2 eV corresponded to C–O and CO in the NFC molecule. , …”
Section: Resultssupporting
confidence: 72%
“…Additionally, the corresponding atomic content of C and N increased (Table S1) compared with TiO 2 , which could be attributed to the successful binding of the NFC molecule. The high-resolution XPS spectra of Ti in NFC/TiO 2 (Figure 2g) exhibited binding energies at 464.1 and 458.4 eV, ascribed to Ti 2p 47,48 Figure S9 illustrates the absorption spectra of TiO 2 and NFC/TiO 2 . The incorporation of NFC did not alter the absorption spectrum of TiO 2 but instead generated a new absorption peak at approx.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous studies have shown that a series of carbon nanomaterials possess inherent peroxidase activity ( Sun et al, 2015 ; Liu et al, 2023 ). CDs possess high enzymatic activity due to their small size, good biocompatibility, and tunable surface.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that a series of carbon nanomaterials possess inherent peroxidase activity (Sun et al, 2015;Liu et al, 2023).…”
Section: Photodynamic Efficiency Of Mn-cds and Cds In Vitromentioning
confidence: 99%
“…Moreover, CDs possess excellent reactivity and unique photoluminescence properties because the nanoparticle surface is easily modified by various functional groups. When the analyte binds with the surface groups, distinct color and fluorescence changes are observed. , These virtues promote the diverse applications of CDs, including in biological imaging and chemical detection. , Depending on their composition and structure, CDs can be categorized into several types including graphene quantum dots (GQDs), graphitic carbon nitride quantum dots (CNQDs), carbon quantum dots (CQDs), carbon nanodots (CNDs), and carbonized polymer dots (CPDs) . CPDs are a new member of the CD family and possess a hybrid structure consisting of a carbon core and functional groups/polymer chains on the surface due to the low degree of carbonization during their preparation process .…”
Section: Introductionmentioning
confidence: 99%